Analisis Potensi Dampak Erupsi terhadap Pengembangan Sport Tourism pada Kawasan Taman Nasional Gunung Merapi - Damanik, Ruth Shinta; Safari, Indra; Novarlia, Irena; Putra, Gilang Pratama (EduInovasi: Journal of Basic Educational Studies, 2026)
Mount Merapi is one of the most active volcanoes in Indonesia, attracting significant attention for the development of natural and sport tourism attractions in the Mount Merapi National Park (TNGM). However, high volcanic activity and periodic eruptions have led to various multidimensional impacts that could potentially impact the future sustainability of the tourism sector. This study aims to identify and analyze the potential impacts of eruptions on the development of sport tourism destinations in the Mount Merapi National Park area. This research was implemented using a descriptive qualitative method with a case study approach in the affected area. Comprehensive data collection was conducted through participatory observation, in-depth interviews, and documentation involving various stakeholders, including TNGM managers, private tourism destination managers, service providers, local communities, and tourists. Data analysis was conducted systematically using data reduction techniques, data presentation, and conclusion drawing, combined with SWOT analysis to formulate strategies. The results of this study indicate that eruptions have had direct negative impacts in the form of infrastructure damage and the closure of high-risk activity routes, as well as indirect impacts such as decreased visitation due to increased perceptions of security risks. On the other hand, the eruption has been shown to have a positive impact through the formation of a new volcanic landscape, which has sparked increased interest in disaster mitigation-based adventure and educational tourism (Volcano-Sport-Edu). In conclusion, the development of sports tourism in TNGM requires adaptive management strategies, strong cross-sector collaboration, and the integration of sustainable disaster management to ensure the safety, environmental conservation, and economic well-being of local residents.